ANALYSIS OF CONSUMER PREFERENCE OF SUV CAR IN MANADO USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD (CASE STUDY BETWEEN TOYOTA FORTUNER, MITSUBISHI PAJERO, AND HONDA CRV) - Tumuju, Gerald Fandy; Lapian, S.L.H.V. Joyce; Tumbuan, W.J.F Alfa (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Sport Utility Vehicle (SUV) car is existed in Indonesia. A Sport Utility Vehicle (SUV) is a vehicle similar to a station wagon or estate car that is usually equipped with four-wheel drive for on-road or off-road ability. This research aims to analyze the most important criteria for customer to choose the SUV car and the most preferable SUV car for customer. This research used analytical hierarchy process with sample is 40 respondends that were obtained from citizen in Manado. The result from this research shown that safety, quality, and comfortable are the most important things that influence consumer in selecting a SUV cars particularly in Manado Ana Toyota Fortuner become the most preferred SUV cars by the consumer. Every car company in Manado have to pay attention seriously toward this factor. Consumer will seek an SUV car with a good quality and best safety for the product. Mitsubishi Pajero and Honda Cr-v as the competitors of Toyota Fortuner, have to improve their performance that can attract more customer, especially for some criteria that make customer tend to choose Toyota Fortuner.Â Keywords: consumer preference, ahp, suv car